2001
DOI: 10.1164/ajrccm.164.10.2101140
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Pulmonary Vasculature and Decreased Vascular Endothelial Growth Factor, Flt-1, and TIE-2 in Human Infants Dying with Bronchopulmonary Dysplasia

Abstract: An abnormal pulmonary vasculature may be an important component of bronchopulmonary dysplasia (BPD). We examined human infant lung for the endothelial cell marker PECAM-1 and for angiogenic factors and their receptors. Lung specimens were collected prospectively at approximately 6 h after death. The right middle lobe was inflation fixed and part of the right lower lobe was flash frozen. We compared lungs from infants dying with BPD (n = 5) with lungs from infants dying from nonpulmonary causes (n = 5). The BPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
411
2
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 554 publications
(449 citation statements)
references
References 37 publications
27
411
2
9
Order By: Relevance
“…Inhibition of angiogenesis reduces alveolarization (25) and VEGF expression is decreased in infants dying of BPD (26). As previously reported (27), we found suppression of VEGF expression in newborn rat lungs during hyperoxia.…”
Section: Discussionsupporting
confidence: 90%
“…Inhibition of angiogenesis reduces alveolarization (25) and VEGF expression is decreased in infants dying of BPD (26). As previously reported (27), we found suppression of VEGF expression in newborn rat lungs during hyperoxia.…”
Section: Discussionsupporting
confidence: 90%
“…RDS predisposes to BPD, whose pathogenesis resembles, to some extent, that of retinopathy of prematurity, in which high oxygen levels lead to disruption of VEGF-maintenance of blood vessels and endothelial cell apoptosis, resulting in organ damage. In fact, the expression of HIF-1α, HIF-2α, and downstream angiogenic growth factors (VEGF, PECAM-1, Flt-1, and Tie-2) are decreased in animal models of RDS or BPD [24][25][26][27]. Several of adolescent and adult BPD patients exhibit an emphysematous phenotype, potentially related to disruption of alveolar maintenance (see emphysema, below).…”
Section: Hypoxia Signaling In the Lungmentioning
confidence: 99%
“…4 Until recently, the effects of iNO on vascular tone and ventilation perfusion matching were assumed to be responsible for its benefit, 5 but recent animal model investigation has shown that deficient endogenous NO disrupts pulmonary parenchymal and vascular development and that exogenous NO may benefit the developing lung by its effects on vascular remodeling, inflammation and pulmonary edema, lung mechanics, lung growth, angiogenesis and airway smooth muscle. [6][7][8][9][10][11][12][13][14][15][16][17] Despite these intriguing animal model findings, the benefit of iNO in premature infants has not been consistently demonstrated in randomized clinical trials. Several small trials demonstrated an increase in oxygenation with iNO therapy, but no significant impact on the primary endpoints of death and/or BPD was demonstrated.…”
Section: Introductionmentioning
confidence: 99%